Health Status and the Allocation of Time: Cross-Country Evidence from Europe - J. Ignacio Gimenez-Nadal; José Alberto Molina (Institute for the Study of Labor (IZA), 2014)
This paper analyzes the relationship between reported health status and time allocation decisions in six European countries. Using the Multinational Time Use Study, we find that a better perception of own health is associated with less time devoted to sleep, personal care, and non-market work, for both men and women, and with less time in leisure for men, while it is associated with more time in market work for both men and women. We also find that the relationship with activities is very similar across countries, and that market work has a relationship of substitution with sleep, personal care, non-market work, and leisure, with mixed evidence for the rest of the uses of time. These findings are consistent with prior results regarding health, market work, and leisure in the US. However, in contrast to the large positive correlation between health and home production in the US, we find a large negative correlation between these activities in the six European countries analyzed. This study represents a first step in understanding cross-country differences in the relationship between health status and time devoted to a range of activities, in contrast with other analyses that have mainly focused only on market work. A better understanding of these cross-country differences may help to identify the effects of public policies on individual uses of time.
Keywords: D13; J16; J22; 330; health; time allocation; Multinational Time Use Study